Reinforcing EU governance in times of crisis: the Commission proposals and beyond - Belke, Ansgar (Berlin, 2010)
"The recent extensive package introduced by the Commission is the "most comprehensive reinforcement of economic governance in the EU and the euro area since the launch of the Economic and Monetary Union. Broader and enhanced surveillance of fiscal policies, but also macroeconomic policies and structural reforms are sought in the light of the shortcomings of the existing legislation. New enforcement mechanisms are foreseen for non-compliant Member States. In this very crucial and important package of 6 legislative dossiers this paper paper tries to identify critical missing or redundant and/or unworkable elements within the Commission package. Moreover it checks what (if anything) is missing outside and beyond the proposals in order to make the whole package of governance reform complete and workable as, for instance, crisis resolution mechanisms and debt restructuring, EMF, project bonds and Eurobonds."